Running mad for Kentucky : frontier travel accounts - Eslinger, Ellen, 1956- (University Press of Kentucky, 2011)
The crossing of America's first great divide -- the Appalachian Mountains -- has been a source of much fascination but has received little attention from modern historians. In the eighteenth century, the Wilderness Road and Ohio River routes into Kentucky presented daunting natural barriers and the threat of Indian attack. Running Mad for Kentucky brings this adventure to life. Primarily a collection of travel diaries, these day-to-day accounts illustrate the dangers thousands of Americans, adult and child, black and white, endured to establish roots in the wilderness. Ellen Eslinger's vivid a.